2015
DOI: 10.17507/tpls.0505.20
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Communicative Language Teaching and Its Application in China

Abstract: Abstract-The emergence of English as a global language has imposed a profound influence on the methodology of foreign language teaching. Communicative Language Teaching, an influential approach in language teaching, came into being decades ago and later was introduced into China. Nowadays, it has become one of the most important approaches in the field of foreign language teaching worldwide. The present paper discussed the historical and theoretical background of Communicative Language Teaching and its two ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…As a sociolinguist, Hymes had a significant impact on CLT. Similarly, Richards and Rodgers (1986), cited in Liu (2015), stated that CLT dates back to the transformation in language teaching traditions of Britain in the late 1960s. That time was considered the end or ancient time of situational approach.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As a sociolinguist, Hymes had a significant impact on CLT. Similarly, Richards and Rodgers (1986), cited in Liu (2015), stated that CLT dates back to the transformation in language teaching traditions of Britain in the late 1960s. That time was considered the end or ancient time of situational approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both writers assert that by implementing the CLT approach, students' speaking in cognitive and behavioural aspects will be improved. CLT has attracted thousands of attention in the scope of language teaching and has brought much debate with itself (Liu, 2015). Wilkins (1974) was the first person to use the term 'communicative approach' cited in Al-Amara and Alabbad (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Hattani (2018) in his study in Morocco showed the communicative language teaching was as an outstanding instructional approach for the Moroccan EFL classroom and it was able to improve students' English language oral proficiency. Sreehari (2012: 92) in Saudi Arabia, Liu (2015Liu ( : 1051 in China, and Abe (2013) in Japan depicted that CLT was able to facilitate students to learn better in ELT classes. Many EFL teachers adapted the CLT instruction to achieve the goals of language teaching and learning.…”
Section: Communicative Language Teachingmentioning
confidence: 99%
“…Most Chinese teachers are in favor of traditional pedagogical approaches like the grammar-translation method and audio-lingual method that allow teachers maximum control and opportunity to transmit knowledge (Barnard, Richards, & Rodgers, 2002;Hu, 2002;Wen & Clé ment, 2003). Although the CLT and TBLT approaches were introduced and advocated in China many decades ago, the emphasis is on traditional Chinese education which maintains a hierarchical but harmonious relation between teachers and students (Liu, 2015;D. Zhang, Li, & Wang, 2013).…”
Section: Statement Of Problemmentioning
confidence: 99%